Implementing Prudent Healthcare in the NHS in Wales; what are the barriers and enablers for clinicians?. Issue 1 (24th August 2018) - Addis, Samia; Holland‐Hart, Daniella; Edwards, Adrian; Neal, Richard D.; Wood, Fiona
Abstract: Rationale: Prudent Healthcare is a strategy adopted by the Welsh Government in response to the challenge of improving health care during times of austerity and when needs and demand are rising. Four principles underlie Prudent Healthcare: to achieve health and wellbeing through co production; care for those with the greatest health needs first; do only what is needed; and reduce inappropriate variation. For Prudent Healthcare to be implemented in Wales, it is necessary for health professionals to adopt these principles in practice. Objective: This paper reports a qualitative evaluation of clinicians' awareness, experiences, and views about Prudent Healthcare, identifying barriers and enablers to implementation from the clinician's perspective. Methods: Semi‐structured interviews ( n  = 28) and five focus groups (with 23 participants) were undertaken with a diverse range of health professionals working in primary and secondary care. Analysis was underpinned by the COM‐B model which provides a framework to understand behaviour change in context using three domains, Capability, Opportunity, and Motivation. Results: Clinicians reported the importance and challenges of accessing and sharing information and evidence to inform practice (Capability). Reduced staffing levels and service availability were highlighted as possible barriers to Prudent Healthcare implementation while multidisciplinary working and reorganization of staff roles and services were considered enablers (Opportunity). Finally, although the principles of Prudent Healthcare were broadly welcomed (Motivation), a lack of awareness of the initiative and the management of patient expectations presented barriers. Conclusion: While there was a positive response and widespread support for the principles of Prudent Healthcare by clinicians, increasing awareness of the initiative and improvement to systems to enable information sharing and the monitoring of patient outcomes could improve the consistency of implementation.